Danse Macabre - Atilano, Ronald Araña (Likhaan: The Journal of Contemporary Philippine Literature, 2024)
"Danse Macabre" is an ekphrastic poem on Bruegel's “Triumph of Death" and speaks of the irony in creating art at a time of untold suffering and death.